Pengaruh Media Ular Tangga Digital terhadap Kemampuan Operasi Hitung Penjumlahan pada Siswa Disabilitas Rungu Kelas VIII - Lailatul Maghfiroh; Nostalgianti Citra Prystiananta; Khusna Yulinda Udhiyanasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effect of use of digital snake and ladder media on the ability of summation calculation operations in grade VIII hearing impaired students at SLB Delta Sejahtera. The research uses the Single Subject Research (SSR) approach with an A–B design consisting of the baseline phase and the intervention phase. The subject of the study was one deaf student who had difficulty in simple addition calculation operations. Data were collected through a written test at each session and analyzed using visual analysis including directional bias, stability, level change, and data overlap. The results showed that the summation ability in the baseline phase was at a percentage of 30%, 30%, 30%, 40%, 30% and tended to be stable, while in the intervention phase there was an increase in score to reach 90% with a change in level of +50 points and an overlap percentage of 10%. These findings show that digital snake and ladder media have a positive effect on the ability of tabulation operations of students with hearing disabilities. Keywords: Digital Snake Ladder Media, Addition Counting Operation, Hearing- Impaired Student